Awareness of Mothers about Vaccinations on their Children under Five years at Al-Salam Health Center for Primary Health Care in Kirkuk City - Eman Abbass Ahmed; Mona Jihad Saeed (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Vaccination is the most widely used approach in immunization, and immunization is one of the public health programs that prevents disease in society. The process comprises injecting a vaccine into the body to boost immunity against bacteria, viruses, parasites, and fungus. Objective: The object of the study is to assess mother awareness about vaccination to their children under five years at Al-Salam health center for primary health care. Methods: Descriptive study was conducted from November 27th 2022 to 18st June 2023 in order to assess awareness of mothers about vaccinations on their children under five years at Al-Salam health center for primary health care in Kirkuk city. A non-probability sample of (600) mothers was selected. The data were collected through the application of a validated questionnaire, in two parts, the first part related to social and demographic data of study sample, and the second part related to assessment of mothers knowledge regarding to vaccination to their children. Result: Shows that (53.3%) of children were males, (56.7%) were less than 1 year old, and (40%) of the children the first between family members. in regard with mothers aged between 20-26 years, graduated from colleges, and (93%) were married. Most children had taken previous vaccines, with (98.3%) having BCG, Polio, Hepatitis B, DTaP, Rota virus, Pneumococcal, measles, Mumps, Measles, Rubella, and rubella. (71.7%) didn’t take rubella vaccine. Conclusion: The study concluded Mothers Awareness regarding to vaccination to their children under five years were moderate.